Context of occurrence and comparative analysis of top lexical phrases in online business letters (OBL) and business letter corpus (BLC): a corpus-based study / Hairul Azhar Mohamad - Mohamad, Hairul Azhar (2015)
This research aims to investigate into the behaviors of lexical phrases in the domain of business letters accessible for free online to the public users. For the present researcher to achieve this, a sample of three-hundred (300) online business letters were selected based on criterion sampling from ten (10) most visited websites across the globe. The data were then extracted with Antonc concordance program for further analyses in order to address three research questions for three research objectives; firstly the frequency counts of five (5) types of lexical phrases in six (6) types of online business letters available on ten (10) most-visited business correspondence websites; secondly, the contexts of occurrence for top 5 lexical phrases in five (5) types of lexical phrases from online business letters available on ten (10) most-visited business correspondence websites and finally the ways the types of lexical phrases in these sample online business letters of these websites differ from Business Letter Corpus (BLC). It was found that more number of words in a letter did not signify more lexical phrases. The order of the most frequent to the lowest counts of lexical phrases was identified as Sentence Builders, Collocations, Deictic Locutions, Polywords and Institutionalized Utterances (IU). Out of all lexical phrases found, 53 percent was found to be sentence based than word/phrase-based. All lexical phrases occurred in the active voice construction and most of the lexical phrases were dominant in the opening and closure of business letters. On the comparative analysis, out of fifteen (15) lexical phrases, ten (10) similar lexical phrases were found in both online business letters and Business Letter Corpus (BLC). This study will be significant in eventually producing a list of top phrases from the five (5) types of lexical phrases for academic reference. It gives further insight into the course designers and academic teachers on online business letters. It also allows them to understand the degree of usefulness of online business letters as their samples for English for Specific or Occupational Purposes. Pedagogical implications and future research considerations were discussed in the final part of the research.